Reduction of structural noise inside crane cage by piezoelectric actuators - FEM simulation - Marek S. KOZIEŃ; Jerzy WICIAK (Archives of Acoustics)
In the paper the finite element simulations of the reduction of the noise inside the crane cage by piezoelectric actuators glued to chosen external walls is discussed. The whole cage structure and internal acoustic medium is modelled and piezoelectric elements are dispersed. The first two lower natural frequencies are considered. The completely different results of reduction are obtained for the analysed modes. The aim of the analysis is to show the possibility of application of piezoelectric elements to active noise and vibration cancellation for the realistic machine structure as crane cage.